Blockchain-Assisted Distributed Fog Computing Control Flow Attestation. (28th August 2022) - Li, Hongchao; Shen, Tao; Bai, Fenhua; Gong, Bei
Abstract : The control flow hijacking attack poses a serious threat to the integrity of the software. The attacker exploits the loophole to hijack the control flow of the running program to achieve the purpose of the attack. Remote control flow attestation is a method for embedded devices to ensure the integrity of the software. With the continuous development of Internet of Things (IoT) technology, embedded devices have exploded. None of the existing control flow attestation schemes can adapt to the real-time attestation requests of such massive embedded devices. This paper proposes a blockchain-assisted distributed fog computing control flow attestation scheme BDFCFA to deal with this scenario. The scheme uses a simplified control flow representation model, which can effectively represent the control flow of the program and reduce the runtime overhead of the prover in the attestation process. We use SGX technology to protect the integrity and confidentiality of verifier and prover data during the attestation process. Our proposed bidirectional control flow attestation protocol based on the elliptic curve can greatly protect the communication security between verifiers and provers without incurring excessive performance overhead and communication cost. We evaluate the performance of BDFCFA through the SNU real-time benchmark and demonstrate that BDFCFA has better performance. Finally, compared to the existing remote control flow attestation scheme, the results show that BDFCFA has the highest security.